2018
DOI: 10.1186/s12885-018-4912-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncological safety of autologous breast reconstruction after mastectomy for invasive breast cancer

Abstract: BackgroundThe number of patients requesting autologous breast reconstruction (ABR) after mastectomy for breast cancer has increased over the past decades. However, concern has been expressed about the oncological safety of ABR. The aim of our study was to assess the effect of ABR on distant relapse.MethodsIn this retrospective cohort study, data was analysed from patients who underwent mastectomy for invasive breast cancer in University Hospitals Leuven between 2000 and 2011. In total, 2326 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…However, to date, no randomized controlled data on the differences in the oncologic safety between mastectomy with breast reconstruction and without breast reconstruction or the oncologic outcomes of different reconstruction methods is available due to ethical concerns. Most existing studies based on retrospective data have documented that both IBR and AFR did not increase the risk of breast cancer recurrence [8][9][10][11][12]. However, con icting results have indicated that postmastectomy AFR has an increased risk of cancer recurrence compared with mastectomy alone [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, no randomized controlled data on the differences in the oncologic safety between mastectomy with breast reconstruction and without breast reconstruction or the oncologic outcomes of different reconstruction methods is available due to ethical concerns. Most existing studies based on retrospective data have documented that both IBR and AFR did not increase the risk of breast cancer recurrence [8][9][10][11][12]. However, con icting results have indicated that postmastectomy AFR has an increased risk of cancer recurrence compared with mastectomy alone [25].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, postmastectomy reconstruction options mainly include implant-based reconstruction (IBR) and autologous ap reconstruction (AFR) in the current clinical practice. Previous studies have demonstrated that breast reconstruction using either implants or autologous tissue does not increase the risk of breast cancer recurrence compared to conventional mastectomy without reconstruction [8][9][10][11][12]. However, few studies have compared breast cancer outcomes between the IBR and AFR [13].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic and Reconstructive Surgery, Yokohama City University Medical Center, Yokohama, Japan. 3 Diagnostic Pathology, Yokohama City University Medical Center, Yokohama, Japan. 4 Department of Gastroenterological Surgery, Yokohama City University Graduate School of Medicine, Yokohama, Japan.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…It is an integral part of the breast reconstruction process, as patients associate this stage with the end of their plastic surgery treatment and a sense of completion [ 2 ]. It was once a concern that surgical trauma could activate dormant micrometastases; however, more recent reports have shown no increased risk of breast cancer recurrence following breast reconstruction [ 3 ]. New primary carcinomas arising from the grafted breast tissue have rarely been reported following surgery for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive and prolonged autologous breast reconstructive surgery may be considered a major tissue trauma suggesting autologous breast reconstruction increases the breast cancer recurrence risk. However, studies have shown different results [12][13][14][15], probably owing to inclusion of heterogenous breast reconstructive surgery and lack of homogeneous study populations.…”
Section: Introductionmentioning
confidence: 99%